Fast numerical methods for image restoration - Shi, Juan (2012)
In the computer vision field, most problems can be described as energy functionals. The optimums of these energy functionals are the solutions of the computer vision problems. The fast numerical methods seeking the solutions are fundamentally important and highly demanded.